Correction to: Parma consensus statement on metabolic disruptors - Jerrold J. Heindel; Frederick S. vom Saal; Bruce Blumberg; Patrizia Bovolin; Gemma Calamandrei; Graziano Ceresini; Barbara A. Cohn; Elena Fabbri; Laura Gioiosa; Christopher Kassotis; Juliette Legler; Michele La Merrill; et al. (BMC, 2017)
Correction After publication of the article [1], it has been brought to our attention that the thirteenth author of this article has had their name spelt incorrectly. In the original article the spelling "Laura Rizzir" was used. In fact the correct spelling should be "Laura Rizzi".